Diversifikasi peningkatan kualitas dan perluasan pemasaran produksi industri tenun sutera - Moh. Thamrin Mappalahere (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The problems in VMT program are 1) the partnerindustry does not know variety of motif designs and does notrecognize color dyeing techniques using Indogosol dyes thatcan last longer and do not fade and 2) the partner industry onlyused limited range of colors. The Multi-Year Vucer Programaims to improve the quality of product design and silkcoloring, to develop silk color variations as an effort toincrease sale production and to introduce color dyeing usingIndogosol which utilizing the sunlight in the process ofcoloring. This effort is carried out as an effort to increaseselling value and production of silk and weaving businesslocated in Sempange village of Tana Sitolo district in Wajoregency. The method used in this program were lectures,discussion, demonstration and question and answer session.The results showed that the small-scale industry can makevaried motif designs with coloring techniques using Indogosoldyes that are resistant and can increase their sale productionand they finally able to develop color variations according toconsumer needs and trends in market as an effort to increasethe sale value of export products.